A study on the performance of University Malaya campus bus service using dwell time model and passenger distribution analysis / Gan Jia Jiun - Gan, Jia Jiun (2020)
Accessibility and mobility are key to a sustainable transport system for the community within a green university campus. To encourage more sustainable transport usage, public transport such as campus bus service are provided for students to commute between academic buildings and residential areas on campus. The current operating timetable of the campus bus service is made by the Student Affairs Division based on the observation of bus service in the past few years. This research aimed to study the capability of the campus bus service in University of Malaya (UM) to accommodate the demand of students. A survey questionnaire was distributed among students to identify their transportation mode, willingness and satisfaction level on current campus bus service. To identify the congruity and appropriateness of the current bus timetable, a passenger count survey was done to identify the distribution of passenger demand. The passenger count data was analysed with respective bus capacity to obtain the passenger load factor (PLF). PLF was used to identify the capability of the current bus service to cater to passenger demand. Besides, the bus trip time data was analysed with passenger count data to study and evaluate the effectiveness of the campus bus service. Other than the number of passengers boarding and alighting, the station type, bus type used, and PLF also affected bus dwell time. A statistical software, Minitab was used to construct dwell time models through multiple linear regression analysis and examine the effect of PLF on dwell time. Bus timetable optimisation was used to generate a demand-based bus timetable for the UM campus bus routes. The proposed bus timetable has shorter dwell time and passenger waiting time than the current bus timetable. By implementing the proposed optimal bus timetable, the transit capacity, speed, and reliability of UM’s campus bus service can be enhanced.